UJI SITOTOKSIK FRAKSI ETIL ASETAT EKSTRAK ETANOL AKAR PASAK BUMI (eurycoma longifolia jack) TERHADAP SEL KANKER T47D DENGAN METODE 3-(4,5 dimetiltiazol -2-il)2,5 difenil tetrazolium bromide (MTT) - Mahfur Mahfur (LPPM Universitas Pekalongan, 2016)
Cancer is one of the leading causes of death in the world, there were 14.1 million cancer cases and 8.2 million of them cause deaths occurred in 2012. The data from BPJS, in January-June 2014 were reported for outpatient treatment of cancer ranks second with 88.106 the number of cases, while for inpatient ranks 5th, with the number of 56.033 cases. Of the many types of cancer, breast cancer is a common malignancy and a major cause of death in women. Chemotherapy is a cancer treatment using a drug that destroy cancer cells. Anticancer drugs in question are cytotoxic drug (a chemotherapeutic agent) such as taxol, bleomycin, doxorubicin, 5-flurourasil, chlorambucil. The actifity of cytotoxic drug is not selective, because they are either toxic to cancer cells and normal cells. Other treatments that can be used to terapy of cancer is using natural product. Eurycoma longifolia Jack is one plant native of Indonesia which has anti-cancer potential. One of The compounds that have the ability cytotoxic is euricomanone. This study aims to determine Cytotoxic effects of ethyl acetate fraction ethanol extract of Eurycoma longifolia Jack to T47D cancer cells by the method of MTT. The sample used are the roots of Eurycoma longifolia Jack, as much as 500g sample were extracted with ethanol. The extract obtained is then fractionated using ethyl acetate solvent. The fractions obtained tested cytotoxic ability by the method of 3- (4,5 dimetiltiazol -2-yl) - 2,5 diphenyl tetrazolium bromide (MTT) to determine IC50 value. The yield resulting from the extraction process was 2.99% or 14,95 g. ethyl acetate soluble fraction amounted to 19.73% from the totally extract. MTT assay results showed IC50 ethyl acetate fraction of ethanol extract Eurycoma longifolia Jack at 340 µg / ml